The efficacy and safety of thrombopoietin receptor agonists in solid tumors with chemotherapy-induced thrombocytopenia: a systematic review and network meta-analysis of randomized controlled trials - Lai, Yingyu; Pan, Qianni; Wang, Shiyu; Luo, Qingmao; Huang, Zhencong; Wei, Mingzhong; Jiang, Zhouqian; Yi, Wenyan (Frontiers in Pharmacology, 2025)
ObjectiveThe objective of this study was to compare and rank the efficacy and safety of different thrombopoietin receptor agonists (TPO-RAs) in the treatment of chemotherapy-induced thrombocytopenia (CIT) among patients with solid tumors.MethodsPubMed, Cochrane Library, Embase, MEDLINE, Web of Science, ClinicalTrials.gov, CNKI, Wanfang Database, VIP Database, SinoMed, and China Drug Trials (www.chinadrugtrials.org.cn) were searched for randomized controlled trials (RCTs) of TPO-RAs for CIT in solid tumors from the inception to 31 December 2024. The Cochrane Risk of Bias Assessment Tool 2 was used for assessing the risk of bias. We performed a random-effects network meta-analysis using STATA 14.0 software. Treatments were ranked according to the surface under the cumulative ranking curve. Confidence of the evidence was assessed using Confidence in Network Meta-Analysis. The study protocol was registered with PROSPERO (number CRD42024612536).ResultsA total of eight studies (568 patients) were included. Most RCTs (7/8) showed a low risk of bias. The confidence in evidence was often low or very low. Our network meta-analysis indicates that when compared with placebo, hetrombopag (summary RR 0.45, 95% confidence interval 0.28–0.73) and eltrombopag (0.57, 0.41–0.81) significantly reduced the incidence of chemotherapy dose reduction or delay due to thrombocytopenia. Hetrombopag (0.29, 0.13–0.68) also significantly reduced the platelet transfusions. Eltrombopag had the lowest risk for bleeding event (0.41, 0.13–1.23) and mortality (0.83, 0.48–1.44). There were no significant differences in the risk of adverse events (AEs) between interventions. Hetrombopag (0.37, 0.02–8.68) showed the least risk of thrombosis. According to rankograms, hetrombopag was ranked as the best for reducing the incidence of chemotherapy dose reduction or delay, and platelet transfusions, with the least risk of serious AEs and thrombosis. Eltrombopag carried the least risk of bleeding events and mortality.ConclusionOur network meta-analysis suggested that based on the limited indirect data, hetrombopag may represent the preferred therapy for avoiding chemotherapy dose reductions or delays and platelet transfusion. Eltrombopag may be considered the preferred therapeutic option for avoiding bleeding events and mortality. Both compounds have acceptable safety profiles. However, larger head-to-head trials are needed to confirm these findings.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024612536, identfier CRD42024612536.